Pengaruh Literasi Keuangan, Pendapatan Dan Gaya Hidup Terdadap Pengelolaan Keuangan Oleh Pelaku Usaha Kecil Menengah Di Kecamatan Sumberrejo - Fadia Ika Nurwahyuni; Wisnu Panggah Setiyono; Sriyono Sriyono (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine the influence of financial literacy, income and livelihood on the financial management of tobacco business actors in Bojonegoro Regency. This type of research is quantitative research and the data used are primary data obtained from questionnaires, observations and interviews. The population of this study is tobacco farmers in Bojonegoro using a sample of 393 respondents. The sampling technique is probability sampling. The analysis method uses multiple linear regression. The results of the study show that: (1) financial literacy has a positive and significant effect on the financial management of tobacco business actors. (2) income has a positive and significant effect on the financial management of tobacco business actors. (3) lifestyle has a positive and significant effect on the financial management of tobacco business actors (4) financial literacy, income and lifestyle have a positive and significant effect on tobacco business actors.